Role of Cellular Immunity in Cow's Milk Allergy: Pathogenesis, Tolerance Induction, and Beyond. (6th June 2014) - Jo, Juandy; Garssen, Johan; Knippels, Leon; Sandalova, Elena
Abstract : Food allergy is an aberrant immune-mediated reaction against harmless food substances, such as cow's milk proteins. Due to its very early introduction, cow's milk allergy is one of the earliest and most common food allergies. For this reason cow's milk allergy can be recognized as one of the first indications of an aberrant inflammatory response in early life. Classically, cow's milk allergy, as is true for most other allergies as well, is primarily associated with abnormal humoral immune responses, that is, elevation of specific immunoglobulin E levels. There is growing evidence indicating that cellular components of both innate and adaptive immunity play significant roles during the pathogenesis of cow's milk allergy. This is true for the initiation of the allergic phenotype (stimulation and skewing towards sensitization), development and outgrowth of the allergic disease. This review discusses findings pertaining to roles of cellular immunity in allergic inflammation, and tolerance induction against cow's milk proteins. In addition, a possible interaction between immune mechanisms underlying cow's milk allergy and other types of inflammation (infections and noncommunicable diseases) is discussed.